(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The kinetics and mechanism of interaction of pyridoxal with structurally differentamino acids were studied under various conditions (pH media, solvent, temperature). The study of the effect of temperature on the rate of condensation of amino acids with pyridoxal at the stage of dehydration of amino alcohols showed that the rates increase with increasing temperature. The activation energies of the dehydration stage of amino alcohols are calculated. (Eact= 16.1 Kj/mol).